Writing, producing, and selling your play - Catron, Louis E.; Catron, Louis E. (Englewood Cliffs, New Jersey Prentice-Hall, Inc., 1984)
So you have a desire to create . . . to express your emotions . . . to present your ideas . . . and to entertain.

With this guide at your fingertips, it's not as complicated as you may think to get started . . . to write the play you have within you . . . and get it performed. The most practical book on playwriting available, Writing, Producing, and Selling Your Play features a solid, down-to-earth emphasis on craft and award-winning playwright and instructor at the College of William and Mary, it takes you by the hand to show just what's involved in creating a stageworthy play. It covers everything from basic considerations--including plot and character development, theme, and dialogue--to production and publication of your work. It offers concrete writing guidelines to make your hours at the typewriter much more productive.

In addition, Writing, Producing, and Selling Your Play includes:
-exercises to get you going
-inspirational anecdotes to keep you going (did you know that Eugene O'Neil was a conscientious journal-keeper, and Mourning Becomes Electra was the result of his entries?)
-excerpts from such classics as Macbeth, The Glass Menagerie, and The Dumb Waiter to help you grasp key concepts.

Complete with lists of plays to read for instruction, Writing, Producing, and Selling Your Play is the perfect book for the new generation of Tennessee Williamses and George Bernard Shaws!
Includes index (pages 267-272).
Keywords: Playwriting; Performing arts -- Production and direction